2003
DOI: 10.1161/01.cir.0000058705.97823.f4
|View full text |Cite
|
Sign up to set email alerts
|

Intramural Coronary Vasculature Prevents Transmural Radiofrequency Lesion Formation

Abstract: Background-Blood flow near a radiofrequency (RF) lesion can reduce lesion size by convective cooling. It is unknown whether blood flow through small vasculature within an RF lesion can prevent transmural lesion formation. Methods and Results-In 40 rabbit right ventricle preparations, 2 epicardial RF lesions were created straddling a selectively perfused (0 to 12 mL/min) marginal artery (diameter, 0.34Ϯ0.1 mm). RF lesions were created at either 60°C or 80°C and delivered either sequentially or simultaneously. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 24 publications
(15 reference statements)
4
42
0
Order By: Relevance
“…Our laboratory has shown that cross-sectional area is a determinant of conduction through gaps in RF lesions in the rabbit RV flap preparation. 12 The gap geometry in all of these studies was linear, comparable to the straight gap in our current study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our laboratory has shown that cross-sectional area is a determinant of conduction through gaps in RF lesions in the rabbit RV flap preparation. 12 The gap geometry in all of these studies was linear, comparable to the straight gap in our current study.…”
Section: Discussionsupporting
confidence: 83%
“…12 New Zealand White rabbits (Robinson Services, Inc, Clemmons, NC) were anesthetized with xylazine (7 mg/kg) and ketamine (100 mg/kg), according to American Veterinary Association Panel on Euthanasia guidelines. The hearts were rapidly removed, and the aortic root was perfused under continuous pressure (80 cm H 2 O) with oxygenated Krebs-Henseleit buffer (37°C).…”
Section: Tissue Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, coronary blood flow may shield and cool the subepicardium beneath the vasculature. 27 Alternate energy sources potentially could be more effective. In this study, catheter cryoablation was successful in 1 patient when used as initial therapy but not in a second patient after unsuccessful irrigated-tip radiofrequency ablation.…”
Section: Approaches To Catheter Ablationmentioning
confidence: 99%